Pengaruh Tunjangan Kinerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Pemberdayaan Masyarakat Dan Desa Kabupaten Bima - Muhammad Rehan; Firmansyah Kusumayadi (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of performance allowances and work discipline on employee performance at the Department of Community and Village Empowerment, Bima Regency. The research employed a quantitative approach with a Likert-scale questionnaire as the main instrument. The study population consisted of 62 employees, with a sample of 34 civil servants determined using purposive sampling techniques. Data were collected through observation, interviews, questionnaires, and documentation, and then analyzed using multiple linear regression with SPSS version 26. The findings indicate that performance allowances have a significant effect on employee performance, while work discipline does not have a significant partial effect. However, simultaneously, performance allowances and work discipline significantly influence employee performance.